Deciphering Ligand Controlled Structural Evolution of Prussian Blue Analogues and Their Electrochemical Activation during Alkaline Water Oxidation - Singh B.; Mannu P.; Huang Y.-C.; Prakash R.; Shen S.; Dong C.-L.; Indra A. (My University, 2025)
Herein, we have demonstrated the control over the structure of precatalysts to tune the properties of the active catalysts and their water oxidation activity. The reaction of K3[Fe(CN)6] and Na2[Fe(CN)5(NO)] with Co(OH)2@CC produced precatalysts PC-1 and PC-2, respectively, with distinct structural and electronic features. The replacement of the −CN group with strong π-acceptor −NO modulates the electronic and atomic structure of PC-2. As a result, a facile electrochemical transformation of PC-2 into active catalyst Fe−Co(OH)2-Co(O)OH (AC-2) has been attained only in 15 CV cycles while 600 CV cycles are required for the electrochemical activation of PC-1 into AC-1. The X-ray absorption studies reveal the contraction of the Co−O and Fe−O bond in AC-2 because of the presence of a higher amount of Co3+ and Fe3+ than in AC-1. The high valent Co3+ and Fe3+ modulates the electronic properties of AC-2 and assists in the O−O bond formation, leading to the improved water oxidation activity. © 2022 Wiley-VCH GmbH.